Preparing for Inaugural Convocation (Institutional Knowledge at Singapore Management University, 2007)
A large air-conditioned marquee tent is set up at Bras Basah Park, the site of Singapore Management University’s future city campus. SMU’s inaugural convocation is held here on 29 July 2000.